Editorial - Tuzzo, Simone Antoniaci; Maricato, João Melo; Signates, Luiz; Moraes, Ângela; Borges, Deborah (Comunicação & Informação, 2015)
Editorial Revista 2015.1 – v. 18, nº 2. Comunicação & Informação ISSN versão impressa: 1415-5842 ISSN versão eletrônica: 2317-675X